Synthesis of a [6]rotaxane with singly threaded γ-cyclodextrins as a single stereoisomer - Man, Jason Yin Hei; Au-Yeung, Ho Yu (Beilstein Journal of Organic Chemistry, 2019)
A series of hetero [4]-, [5]- and [6]rotaxanes containing both cucurbit[6]uril (CB[6]) and γ-cyclodextrin (γ-CD) as the macrocyclic components have been synthesized via a threading-followed-by-stoppering approach. Due to the orthogonal binding of CB[6] to ammonium and γ-CD to biphenylene/tetra(ethylene glycol), the [n]rotaxanes display a specific sequence of the interlocked macrocycles. In addition, despite of the asymmetry of γ-CD with respect to the orthogonal plane of the axle, only one stereoisomer of the [6]rotaxane was obtained.
Keywords: cucurbit[6]uril; cyclodextrin; macrocycles; mechanostereoisomer; rotaxane